ANALISIS PENGARUH MANAGE IT HUMAN RESOURCE (PO7) DAN EDUCATE AND TRAINUSERS (DS7) PADA FRAME WORK COBIT 4.1 TERHADAP IT SERVICE MANAGEMENT (ITSM) DI PT SEMEN BATURAJA (PERSERO) TBK - Nasution, Surya Andita; Marnisah, Luis; Zamzam, Fakhry (Jurnal Ecoment Global, 2020)
This research aims to know the impact of "Manage IT Human Resource (PO7)" and "Educate and Train User (DS7)" in COBIT 4.1 on IT Service Management (ITSM) at PT Semen Baturaja (Persero) Tbk, both partially and simultaneously. The population in this research is 787 employee at PT Semen Baturaja (Persero) Tbk who are actively using information technology, chosen by purposively sampling. This research is a quantitative research using survey, descriptive and associative method, also involving doubled linear analysis technique to analyze the data. The test result t partially of Manage IT Human Resource (PO7) and Educate & Train User (DS7) partially impacts on IT Service Management (ITSM) with the test value of thitung 3,920 > ttabel(0,05,n-2) 1,98729 and thitung 4,647 > ttable(0,05,n-2)1,98729. The test result F simultaneously Manage IT Human Resource (PO7) and Educate & Train User (DS7) impacts on IT Service Management with the Fhitung 46,955 > Ftable (2,n-2) as 3,10. Contribution given by Manage IT Human Resource (PO7) and Educate & Train User (DS7) is 51,9% while 48,1% is impacted by other variables. Partially Manage IT Human Resource (PO7) impacts biggest 30,8% and Educate & Train User (DS7) impacts smallest 21,3% on IT Service Management (ITSM). By increasing personnel’s competency of Information Communication and Technology Division, also give the suitable education and training, so the understanding of role, function, authority and responsibility of Information Communication and Technology Division will be increasing, thus, it could present the customer satisfaction of Information Technology Services.Keyword :Manage IT Human Resource (PO7),Educate and Train User (DS7), IT Service Management, COBIT 4.1.